Beyond Feeling "Fine": Mental and Social Well-Being among Generation Z Santri in Pesantren - Rohmah, Robi'atur; Muhammad Muhib Alwi (ANFUSINA: Journal of Psychology, 2026)
Mental and social well-being among adolescents has become an increasingly important concern as young people face growing social, academic, and informational pressures. In Indonesia, santri living in pesantren represent a distinctive subgroup of Generation Z whose daily lives are shaped by religious discipline, communal living, and strong moral values. Although pesantren are widely associated with resilience, discipline, and social cohesion, limited research has examined how santri themselves interpret their mental and social well-being within this context. This study explored how Generation Z santri perceive and interpret their mental and social well-being after living in pesantren for at least six years. A qualitative descriptive design was employed involving five santri in East Java selected through purposive sampling. Data were collected through semi-structured in-depth interviews, non-participant observation, and reflective written responses, and analyzed using thematic analysis. Five interconnected themes emerged: perceived emotional stability, emotional pressure, social belonging, emotional expression, and normalization of distress. Although participants generally described themselves as emotionally stable and "fine," their narratives also reflected various emotional and social challenges that were interpreted as part of everyday adaptation to pesantren life. These findings suggest that mental and social well-being is understood not simply through the absence of emotional difficulties but through participants' ongoing interpretations of their lived experiences within the social and cultural context of pesantren. Based on these findings, this study proposes a tentative conceptual model that portrays well-being as a context-dependent and negotiated experience. The findings highlight the importance of culturally responsive mental health initiatives that support emotional expression while remaining compatible with the educational, religious, and communal values of pesantren. Keywords: Generation Z, Mental health, Pesantren, Santri, Social well-being